(3CMGSf GdeMGed aj TQM GdYhGed GdLQLGfjIs - (3eMeO Hf eMeO Hf eMeO GdeYQha HGHf CejQ MGL hjbGd dg GHf GdehbJ, CHh YHO Gddg, TeS GdOjf , (B879 (3g` s; (3CHh HcQ YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, YHO GdbGgQ GdLQLGfj,J (B471 (3g` s ((3MdH s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO abO SCdJe Cf CYdb eG JjSQ di PcQg Ydi GdfHPI GdeSeGI HGdYhGed ai GdfMh JCdja GdTjN GdEeGe YHO GdbGgQ GdLQLGfi aJhgJ fMh Pdc hCWdJ GdfaS hSejJ gPG GdJYdjb HCMGSf GdeMGed s
(3BNQgG (B:s
(3hgj JbJVi ONhd EKfi YTQ dEWdGbgG ajNa GdCTcGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI LjOI s
(3HBNQgG ELGRI HNW GdeUfa dYdGA GdRjf Ydi Hf GdNhGLG TQa GdOjf ehSi Hf GdNhGLG s
(3dgG fSNI CNQi eagQSI JMJ Qbe (B6 (3fMh s
(3bQf GdfSN (B:s
Keywords: (3GdfMhs